System prawa ochrony zwierząt w Niemczech (zagadnienia ogólne): [System of legal protection of animals in Germany (basic issues)] (Studia Prawnicze / The Legal Studies, 2011)
Celem opracowania jest analiza systemu prawnej ochrony zwierząt obowiązującego w Republice Federalnej Niemiec w oparciu o prawo międzynarodowe, wspólnotowe, a w szczególności prawo wewnętrzne tworzone na szczeblu federalnym. Na wybór analizy prawa niemieckiego wpłynęły względy historyczne i praktyczne. Niemcy jako drugi kraj europejski uregulowały prawną ochronę zwierząt. Pierwszym była Anglia, w której 7 maja 1822 r. przyjęto ogólnopaństwową ustawę dotyczącą ochrony humanitarnej zwierząt zapobiegającą okrutnemu i niewłaściwemu traktowaniu bydła (Act to prevent the cruel and improper Treatment of Cattle) obejmując ochroną konie, bydło oraz owce. Na terenie Niemiec początkowo przepisy karne penalizujące znęcanie się nad zwierzętami pojawiły się w prawach poszczególnych krajów. Ogólnopaństwowa ustawa - Kodeks karny została przyjęta 15 maja 1871 r. Kolejnym krokiem na drodze zwiększenia ochrony zwierząt była ustawa o ochronie zwierząt z 24.11.1933 r., która na terenie Niemiec Zachodnich obowiązywała do 1972 r. Biorąc pod uwagę system prawa precedensowego istniejącego w Wielkiej Brytanii i system prawa stanowionego w Niemczech wydaje się, że analiza ustawodawstwa niemieckiego w zakresie ochrony zwierząt zarówno w aspekcie historycznym, jak i w świetle aktualnie obowiązującego prawa, będzie bardziej przydatna na użytek ewentualnych postulatów kształtowania kierunku polskiej legislacji w tym zakresie. The aim of this paper is to analyse the system of legal protection of animals applicable in the Federal Republic of Germany. In the territory of Germany, the first regulations regarding animal protection were effected in penal law. In the 17th and 18th centuries, animals were sometimes regarded as perpetrators of or associates in crime. In the second half of the 19th century, in the territory of Germany, some provisions penalizing public cruel treatment of animals were introduced into national criminal acts, as it was seen as scandalising. The true nature of the offence was not the very infliction of suffering on animals but doing so in the presence of other people, which meant the protection of morality. The evolution of the German animal protection laws led to animals being regarded as the object of protection. In the period between the passing of the first Animal Protection Act in 1933 and the text of the Act of 1972 currently in effect, the level of animal protection increased significantly, which was due to the new aspects of animal use and the necessity to adapt domestic law to Community law. The 1990 Civil Code amendments provided for the so-called dereification of animals. The separation of animal protection law results from the provisions of Article 20a of the Constitution, which makes animal protection a fundamental task of the State, along with the protection of environment. A systemic approach to animal protection law presumes that a specific structure and internal relationships should be indicated as well as some criteria for ordering a set of animal protection legal norms. Therefore, the paper discusses the object of protection, the aim and the sources of the law as well as the general principles and characteristics of animal protection laws. The object of protection are animals whose nervous system structure allows at least for the awareness of pain. The sources of the law in Germany include the Constitution, international agreements, generally applicable EU law on animal protection and domestic law - mainly the Animal Protection Act. The sources of the law of particular federated states (Bundesländer) have been omitted for the purpose of this discussion because the aim, general principles and characteristics of animal protection law can be sufficiently researched based on the laws of the federal level.The analysis of sources of law allows for the formulation of the following principles of animal protection law:– the State’s obligation to protect animals, – consideration of moral values of animal welfare according to the needs of the species, prevention of suffering and protection of animals’ living space by means of appropriate provisions in environmental laws,– the primacy of human interests over animal protection, – human responsibility for animals,– the prohibition of unjustified infliction of pain, suffering or harm,– prevention,– the comprehensiveness of animal protection,– taking into account species-related and individual differences in maintenance and handling of animals,– higher levels of protection of vertebrate animals.The characteristics of animal protection laws include:– the main goals and objectives are in line with the European trends in animal protection,– the internationalization of the protection,– openness,– a very wide area of regulation, in comparison with the systems of other fields of law,– dynamism,– protection of some animals maintained outside the territory of the European Union.